Methodical Training System Enhancements of Future Biology Teachers at Pedagogical Universities - Hrytsai, Nataliia; Diachenko-Bohun, Maryna; Grynova, Maryna; Grygus, Igor; Zukow, Walery (Journal of History Culture and Art Research, 2019)
Background. Methodical training plays a leading role in future biology specialists’ professional education; it is assumed to be a backbone component of future educators’ professional readiness in modern scientific research. The methodical training of future biology teachers is interpreted as a determined acquisition of methodological knowledge and skills in the context of methodical tasks related to school course of biology and their solving. New tendencies of school biology education development, implementation of innovative pedagogical technologies into teaching process, development of modern training resources provided the necessity to modernize methodical training of future biology educators in pedagogical universities. The objective of this research is giving a scientific ground to the methodical training system of future biology teachers and checking the effectiveness of its implementation at pedagogical universities. Methods. During the implementation of this research the complex of general scientific methods has been used: theoretical ones (scientific literature analysis, terminological analysis, comparison, systematization and generalization of scientific results), empirical ones (observation, discussions, questionnaire, testing for the determination of future biology educators’ method competence level, pedagogical experiment with qualitative and quantitative analysis of results), mathematical statistics method. The total number of 482 students of Ukrainian pedagogical universities were involved in the experiment. Results. After the implementation of pedagogical experiment the number of students with high level of methodical readiness has significantly increased (according to motivation component – by 9,7% cognitive one – by 5,8%, active one – by 6,2%, reflexive one – by 10,5%), with satisfactory level (according to motivation component – by 12,9%, cognitive one – by 25,2%, active one – by 19,3%, reflexive one – by 8,8%); the number of students with low level has decreased respectively (according to motivation component – by 15,9%, cognitive one – by 24,3%, active one – by 20,5%, reflexive – by 11,3%). Conclusion. According to the results of experiment it can be claimed that implementation of future biology teachers’ experimental methodical training system provides the enhancement of students’ methodical proficiency level and higher quality of their professional readiness at pedagogical universities of Ukraine.